2011
DOI: 10.1016/j.carbon.2010.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated graphene sheets decorated with metal/metal oxide nanoparticles: Simple preparation from cation exchanged graphite oxide

Abstract: We produced carbon hybrid materials of graphene sheets decorated with metal or metal oxide nanoparticles of gold, silver, copper, cobalt, or nickel from cation exchanged graphite oxide. Measurements using powder X-ray diffraction, transmission electron microscopy, and X-ray absorption spectra revealed that the Au and Ag in the materials (Au-Gr and Ag-Gr) existed on graphene sheets as metal nanoparticles, whereas Cu and Co in the materials (Cu-Gr and Co-Gr) existed as a metal oxide. Most Ni particles in Ni-Gr w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 32 publications
5
55
0
1
Order By: Relevance
“…The higher NPs size in the graphene-TiO 2 can be attributed to the presence of the twolayer graphene at the pore surface. In particular, it has been previously shown that reduced graphene and graphene oxide structures are not only good substrates for the dispersion of metal NPs, but they also can work as preferential sites for the photo-reduction of metal ions because of the defects which are present in their structure [24,25]. These findings also confirm, although indirectly, that some of the graphene sheets are available on the mesopore surface and are not completely embedded into the pore walls.…”
Section: Resultssupporting
confidence: 74%
“…The higher NPs size in the graphene-TiO 2 can be attributed to the presence of the twolayer graphene at the pore surface. In particular, it has been previously shown that reduced graphene and graphene oxide structures are not only good substrates for the dispersion of metal NPs, but they also can work as preferential sites for the photo-reduction of metal ions because of the defects which are present in their structure [24,25]. These findings also confirm, although indirectly, that some of the graphene sheets are available on the mesopore surface and are not completely embedded into the pore walls.…”
Section: Resultssupporting
confidence: 74%
“…In line with other reports [1,4,5], this strongly suggested for the coordination of GO's oxygen functionalities to the cupric ions, although ion exchange could not be ruled out [6]. In order to obtain direct molecular-level information on the binding mode of copper, we studied the adsorption of Cu(II) 2,2'-bipyridyl complexes of different compositions on GO by electron paramagnetic resonance (EPR) spectroscopy, supplementing the adsorption and X-ray diffraction (XRD) data.…”
supporting
confidence: 75%
“…GO displays a rich oxygen chemistry, which allows its dispersion in aqueous solutions and the interaction with the metal and/or oxide precursors that would improve their dispersion. Several studies can be found concerning the use of GO as support [12], catalyst by its own [13,14]and as precursor of graphene (G) or reduced graphene oxide (rGO) [15]. For this latter approach, both metal/G or metal/rGO [16,17] and metal/oxide/G or metal/oxide/rGO systems [18,19,20] have also been developed.…”
Section: Introductionmentioning
confidence: 99%